Gastric Ectopic Pyloric Opening with Gastric Ulcer: A Rare Case - Myeongseok Koh; Jin Seok Jang (The Korean Journal of Gastroenterology, 2022)
The stomach temporarily stores food and secretes gastric juices to break down and digest food. The normal process is the movement of food digested from the stomach to the duodenum, with the pylorus as a passageway. This paper reports the case of a patient with an ectopic gastric pylorus who presented with gastrointestinal bleeding. A 62-year-old man complained of melena with mild dizziness and nausea. An endoscopic examination revealed a gastric ulcer, approximately 1 cm in diameter, and exposed blood vessels on the posterior wall of the upper body. No normal pyloric structure was observed in the distal antrum, and an opening leading to the duodenum was noted in the posterior wall of the upper body adjacent to the ulcer. This case presents a congenital pyloric ectopic opening in the upper body of the stomach, not in the distal antrum, suggesting a rare gastric morphological variation.